Misery and Economic Growth Nexus in Nigeria; Implications for Electrical Energy Management. Issue 1 (March 2021) - Ubah, J I; Bowale, E K; Ejemeyovwi, J O; Jacobs, I; Adeleye, N; Ihayere, O
Abstract: At first glance, misery seems unquantifiable but has been established to be an aggregation of unemployment and inflation. Nigeria is in a pitiable condition as she is ranked the 6th most miserable country in the world. This study aims to ascertain the effect of economic growth on Misery in Nigeria, that is, to determine whether economic growth rate has strengthened or weakened the misery of Nigerians. This study adopts Autoregressive Distributed Lag (ARDL) model because it considers policy lags of economic phenomena and allows combined order of integrations. The study finds an inverse nexus between economic growth and misery. Hence, recommendations were made in form of measures to ensure the need for economic growth to increase at faster and higher pace to combat high misery levels in Nigeria.